Innovative Pathways for Enhancing Water Productivity in Rice-based systems in Cambodia - Axmed, Maxamed Maxamuud; van Halsema, Gerardo; Urfels, Anton; Flor, Rica Joy; Jayasiri, Nishanka; Ouk, Akhara; Keo, Sokheng; Penn, Navith; Rathmuny, Then (International Rice Research Institute, 2024)
This report summarized research conducted in Prey Veng and Takeo provinces in 2024 as part of a master's thesis (Full Thesis Report) investigating sustainable water resource management for rice-based systems. The research sought to address the following key questions: How do different water management strategies influence water consumption, crop yield, and profitability in rice-based systems amidst climatic variability? And what approaches can be adapted to tackle future climate challenges in order to secure and enhance rice production in Cambodia? Employing a multi-objective conceptual framework (Tang et al., 2023), this study utilized the water-driven productivity model, AquaCrop (Vanuytrecht et al., 2014). AquaCrop was initially calibrated for two short-duration rice varieties and sweet potatoes, followed by the development of five distinct irrigation scenarios.